Pengaruh Disiplin Dan Motivasi Terhadap Kinerja Karyawan Pada CV Nusantara Cipta Pratama Kota Tangerang - Putra, Akbar Aprianto; Rahman, Aan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of Discipline (X1) and Motivation (X2) on Employee Performance (Y) at CV Nusantara Cipta Pratama, Tangerang City. Data were collected through questionnaires distributed to 30 employees at the company’s head office. The data analysis was conducted using IBM SPSS Version 26, and the results indicate that Discipline (X1) has a positive and significant effect on Employee Performance (Y), with a t-value of 2.633 > t-table of 2.052 and a significance level of 0.014 < 0.05. Similarly, Motivation (X2) also has a positive and significant effect on employee performance, as shown by a t-value of 30.031 > 2.052 and a significance level of 0.000 < 0.05. Simultaneously, the F-test results show that both Discipline and Motivation have a positive and significant effect on Employee Performance, with an F-value of 103.950 > F-table of 3.354 and a significance level of 0.000 < 0.05. The study concludes that Discipline and Motivation simultaneously have a positive and significant impact on Employee Performance at CV Nusantara Cipta Pratama in Tangerang City